2007
DOI: 10.1534/genetics.107.076869
|View full text |Cite
|
Sign up to set email alerts
|

Diversification Rates Increase With Population Size and Resource Concentration in an Unstructured Habitat

Abstract: Understanding the mechanisms controlling the generation and maintenance of biodiversity provides some of the planet's greatest and most pressing challenges. Variation in resource concentration, which varies widely at multiple scales, may cause biodiversity to increase, decrease, or exhibit a unimodal response and underlying mechanisms remain obscure. We established experimental cultures of long-term stationary phase (LTSP) Escherichia coli to test whether per capita heterozygosity varies with resource concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…The positive association between SBW25 population size and diversification found in our study (figure 4) provided strong support for the reduction of population size as an important mechanism through which adaptive radiation is inhibited. Similar relationships between population size and diversification have been reported in studies involving SBW25 [37,38] and other diversifying lineages [54,55]. Small population size tends to discourage adaptive radiation for several reasons.…”
Section: Discussionsupporting
confidence: 73%
“…The positive association between SBW25 population size and diversification found in our study (figure 4) provided strong support for the reduction of population size as an important mechanism through which adaptive radiation is inhibited. Similar relationships between population size and diversification have been reported in studies involving SBW25 [37,38] and other diversifying lineages [54,55]. Small population size tends to discourage adaptive radiation for several reasons.…”
Section: Discussionsupporting
confidence: 73%
“…Organisms that capitalize on dense or widespread resources should themselves have high population abundances, with correspondingly greater N e and genetic variation (Stevens et al 2007). It is physically small organisms that can more plausibly achieve and maintain exceptionally large populations (Peters & Wassenberg 1983; Marquet et al 2005).…”
Section: Hyperdiverse Eukaryotes In Naturementioning
confidence: 99%
“…This premise is based on the potential for adaptive mutations arising in a population increasing with the number of reproducing individuals in the population. It has been well established that larger populations generally contain greater genetic diversity than smaller populations, e.g., [73,74] and experimental work with Escherichia coli has demonstrated that increasing population size leads to increased genetic diversity [75] and such diversity is likely to be an important precursor for adaptive speciation. Adaptive genetic evolution was found to increase in eukaryotes as population size increases [76] and, although not all speciation is adaptive, adaptive genetic evolution associated with populations size might be more pertinent to putative links with diversity patterns than is nearly neutral deleterious evolution.…”
Section: Population Sizementioning
confidence: 99%